Functional and pasting properties of wheat/tigernut pomace flour blends and sensory attributes of wheat/tigernut pomace flour meat pie - Ayodele, Idowu Michael (Array, 2019)
This study investigated the functional and pasting properties of wheat and tigernut pomace flour blends, as well as the sensory attributes of the meat pie obtained from the composite flour. Tigernut pomace flour was substituted for wheat flour in the amount of 2 –10%. Unsubstituted wheat flour served as the control. The composite blends were analysed for functional and pasting properties. The sensory attributes of the meat pie obtained from the composite flour were also determined. Bulk density, water absorption capacity, swelling power, and the solubility index of the blends ranged from 0.70 -0.75 g/mL, 0.62 -0.96%, 4.06 -4.47 g/g, and 2.45 -13.7% respectively. Peak, trough, breakdown, final, and setback viscosities, peak time, and pasting temperature ranged from 113.6 -135.9 RVU, 76.7 -90.2 RVU, 36.0 -45.8 RVU, 170 -183.7 RVU, 91.0 -93.6 RVU, 5.07 -6.03 min, and 88.4 -90.0 RVU respectively. In terms of appearance, the meat pie samples prepared from tigernut-substituted flour blends did not show significant difference (p <0.05) from the control sample. The control sample had the highest overall acceptability, although samples from the composite blends were also found to be acceptable. Hence, tigernut pomace flour could be substituted for wheat at the amount of 10% to produce an acceptable meat pie.